Haplotype-Based Noninvasive Prenatal Diagnosis of 21 Families With Duchenne Muscular Dystrophy: Real-World Clinical Data in China - Kong, Lingrong; Li, Shaojun; Zhao, Zhenhua; Feng, Jun; Chen, Guangquan; Liu, Lina; Tang, Weiqin; Li, Suqing; Li, Feifei; Han, Xiujuan; Wu, Di; Zhang, Haichuan; et al. (Frontiers in Genetics, 2021)
Noninvasive prenatal diagnosis (NIPD) of single-gene disorders has recently become the focus of clinical laboratories. However, reports on the clinical application of NIPD of Duchenne muscular dystrophy (DMD) are limited. This study aimed to evaluate the detection performance of haplotype-based NIPD of DMD in a real clinical environment. Twenty-one DMD families at 7–12 weeks of gestation were prospectively recruited. DNA libraries of cell-free DNA from the pregnant and genomic DNA from family members were captured using a custom assay for the enrichment of DMD gene exons and spanning single-nucleotide polymorphisms, followed by next-generation sequencing. Parental haplotype phasing was based on family linkage analysis, and fetal genotyping was inferred using the Bayes factor through target maternal plasma sequencing. Finally, the entire experimental process was promoted in the local clinical laboratory. We recruited 13 complete families, 6 families without paternal samples, and 2 families without probands in which daughter samples were collected. Two different maternal haplotypes were constructed based on family members in all 21 pedigrees at as early as 7 gestational weeks. Among the included families, the fetal genotypes of 20 families were identified at the first blood collection, and a second blood collection was performed for another family due to low fetal concentration. The NIPD result of each family was reported within 1 week. The fetal fraction in maternal cfDNA ranged from 1.87 to 11.68%. In addition, recombination events were assessed in two fetuses. All NIPD results were concordant with the findings of invasive prenatal diagnosis (chorionic villus sampling or amniocentesis). Exon capture and haplotype-based NIPD of DMD are regularly used for DMD genetic diagnosis, carrier screening, and noninvasive prenatal diagnosis in the clinic. Our method, haplotype-based early screening for DMD fetal genotyping via cfDNA sequencing, has high feasibility and accuracy, a short turnaround time, and is inexpensive in a real clinical environment.